Storm surge variation along the coast of the Bohai Sea - Feng, Jianlong (Sci Rep, 2018)
The present study mainly investigates the storm surge variations at different temporal scales using hourly tide gauge data in the Bohai Sea. The seasonal variation, inter-decadal variation, long-term trend and the tide-surge interaction were analyzed separately. The results show that the storm surges in the southwest Bohai Sea are larger than those in the north. The storm surges were more serious in winter (Oct. to Mar.) than in summer half of the year. Significant inter-decadal variations exist in the Bohai Sea, and the extreme storm surge events have been intensifying since 2010. Storm surge intensities at three of the tide gauges (Qinhuangdao, Huludao and Tanggu) exhibited a decreasing trend from 1980 to 2016, with trends significant at the 95% level at Qinhuangdao and Tanggu. Significant tide-surge interactions were observed at all four tide gauges. The tide-surge interaction that results in peak surges mostly occurs during the flood and ebb tides. There is a statistically significant negative correlation between storm surge intensity and the Arctic Oscillation (AO) at Longkou and Tanggu, while there is a significantly positive correlation between storm surge intensity and the Siberian High (SH) at Huludao, Qinhuangdao and Tanggu. A linear regression analysis revealed that the variations of the AO and SH explained 19–48% of the variations in the storm surge intensity in the Bohai Sea.